1999
DOI: 10.1207/s15327957pspr0301_3
|View full text |Cite
|
Sign up to set email alerts
|

Passion, Intimacy, and Time: Passionate Love as a Function of Change in Intimacy

Abstract: To build on existing theories about love, we propose that passion is a function of change in intimacy (i.e., the first derivative of intimacy over time). Hence, passion will be low when intimacy is stable (either high or low), but rising intimacy will create a strong sense of passion. This view is able to account for a broad range of evidence, including frequency of sex in long-term relationships, intimate and sexual behavior of extraverts, gender differences in intimate behavior, gain and loss effects of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
216
1
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(234 citation statements)
references
References 92 publications
(100 reference statements)
10
216
1
7
Order By: Relevance
“…Most people regard it as inappropriate to begin having intense, intimate sexual activity right away, even though some people may feel sexual desire very early in a relationship (e.g., Baumeister & Bratslavsky, 1999;Cohen & Shotland, 1996). Hence, early in a relationship, couples may be restraining their impulses and desires, whereas after they have come to trust each other and establish some degree of intimacy, they may engage in more sexual expression without conflict.…”
Section: Sexual History and Sexual Restraintmentioning
confidence: 99%
“…Most people regard it as inappropriate to begin having intense, intimate sexual activity right away, even though some people may feel sexual desire very early in a relationship (e.g., Baumeister & Bratslavsky, 1999;Cohen & Shotland, 1996). Hence, early in a relationship, couples may be restraining their impulses and desires, whereas after they have come to trust each other and establish some degree of intimacy, they may engage in more sexual expression without conflict.…”
Section: Sexual History and Sexual Restraintmentioning
confidence: 99%
“…Most partners in long-term relationships do behave as expected, however, and, as a consequence, the partners seldom arouse each others' intense emotional passions-either positive or negative. Baumeister & Bratslavsky (1999) propose that degree of passion is a function of a rapid change in intimacy, where "intimacy" is defined similarly to Companionate Love and to Reis & Shaver's (1988) definition of intimacy (i.e., knowledge and understanding of the other combined with communication of a strong positive attitude toward the other). These theorists endorse the generally accepted view that intimacy usually grows gradually, but in those instances in which it rises rapidly, passion should result; in addition, citing Berscheid's model, they predict that when intimacy stabilizes, the relationship should become passionless.…”
Section: Temporal Hypothesesmentioning
confidence: 99%
“…Baumeister and Bratslavsky (1999) reviewed indirect evidence suggesting that rapid increases in intimacy induce positive, relationship-specific emotions such as passion. Karney and Frye (2002) found that married partners base their judg-ments of satisfaction with their relationship more on perceptions of recent improvements than on the quality of the relationship at that particular time.…”
Section: Perceptions Of Goal Progressmentioning
confidence: 99%